Homegrown : Timothy McVeigh and the rise of right-wing extremism - Toobin, Jeffrey (Simon & Schuster, 2023)
"Timothy McVeigh wanted to start a movement. After the Oklahoma City bombing, the Gulf War veteran expressed no regrets. Jeffrey Toobin details how McVeigh's principles and tactics have flourished in the decades since his death in 2001, reaching an apotheosis on January 6 when hundreds of rioters stormed the Capitol. Based on nearly a million previously unreleased tapes, photographs, and documents, including detailed communications between McVeigh and his lawyers, as well as interviews with such key figures as Bill Clinton, Toobin reveals how the story of Timothy McVeigh and the Oklahoma City bombing is not only a powerful retelling of one of the great outrages of our time, but a warning for our future"--